Skepticism and Professionalism to Fraud Detection Ability - Prayoga, Hizkia; Sudaryati, Erina (Journal of Accounting Science, 2020)
This study aims to prove the impact of skepticism and professionalism on the fraud detection ability of internal government auditors in East Java Province. Primary data is usedto obtain data from respondents, namely 102 APIP taken with saturated samples. Thecollected data were then analyzed using SEM PLS version 3.0, where the results provethat skepticism and professionalism has a positive impact on Fraud Detection Ability